2005
DOI: 10.1111/j.1460-2695.2005.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanical and fatigue properties of metallic microwires

Abstract: A B S T R A C TThere is an increasing necessity to record the deformation characteristics of microelements containing freestanding bond wires. The data required are either mechanical or thermal such as Young's moduli, stress-strain values, fatigue-and thermal-strain data, but the nominal strength of a structure changes by scaling its size. Due to this size effect, material data cannot be taken from macrospecimens, thus special testing procedures were introduced. Laser optical sensors based on the speckle corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 27 publications
5
43
0
Order By: Relevance
“…Yang et al 13) showed that the fatigue life of copper wire decreases with a decrease in their diameter from 50 to 30 µm. Weiss et al 14) and Khatibi et al 15) also obtained similar results in the diameter range of 10 to 125 µm. Similarly, Dai et al 16,17) reported that fatigue resistance of copper foils decreases with a decrease in the foil thickness in the range from 20 to 420 µm.…”
Section: Introductionsupporting
confidence: 72%
“…Yang et al 13) showed that the fatigue life of copper wire decreases with a decrease in their diameter from 50 to 30 µm. Weiss et al 14) and Khatibi et al 15) also obtained similar results in the diameter range of 10 to 125 µm. Similarly, Dai et al 16,17) reported that fatigue resistance of copper foils decreases with a decrease in the foil thickness in the range from 20 to 420 µm.…”
Section: Introductionsupporting
confidence: 72%
“…Size reduction generally results in a greater surface area:volume ratio and hence favors tin pest formation on free, but not occluded, surfaces. In contrast, smaller samples are usually associated with higher strengths via reduced grain size 18,19 and would be expected to offer higher resistance to tin pest formation. The existence of fewer grains, as for example in fine wires, introduces a further complexity, because of anisotropy effects.…”
Section: Geometrymentioning
confidence: 97%
“…Size effects on mechanical and fatigue properties of small scaled materials have been subject of numerous investigations [30,31]. A majority of these studies have shown a consistent size effect on the tensile ductility of materials [14,30]. It has been observed that decreasing the ratio of thickness (t) to grain size (d) in thin polycrystalline materials results in a strong reduction of plasticity due to the incompatibility of the neighboring grains and strain localization.…”
Section: Lifetime Modelingmentioning
confidence: 98%
“…Ultrasonic resonance fatigue testing systems, working at about 20 kHz, are frequently used for determination of lifetime curves and studying the crack growth behavior of metallic materials up to gigacycle fatigue regime [12,13]. In addition to the conventionally used dumbbell shaped bulk samples these systems can also be used for testing of special geometries such as thin wires [14], foils [15] and thin walled tubes [16,17].…”
Section: Introductionmentioning
confidence: 99%